Policies on intergroup relations in the cities of CEE countries - Patrycja Matusz Protasiewicz; Josef Kohlbacher (University of Warsaw, Centre of Migration Research (CMR), 2012)
For many years Western European cities have been influenced by the inflow of immigrants from all over the world, having different cultural, religious and linguistic background. Due to this process especially local authorities have been confronted with the need for managing peaceful and successful relations between different groups within the local urban societies. The policy making of intergroup relations in Western European cities has traditionally involved various actors from both native and immigrant groups, acting on behalf of city representatives, NGOs, political parties, labour organizations, churches etc. In comparison with Western European countries, the development of intergroup relations in the metropolises of CEE countries is still in its initial stage because the numerical presence of 'new' immigrant groups is still marginal. In place of immigrants, it is possible to talk about national minorities with differing cultural, religious and linguistic heritage, who settled down in these states as a result of conflict, wars or border changes. This article explores the differences concerning the understanding of 'group' and 'intergroup relations' in four cities of CEE region: Tallinn (Estonia), Wroc±aw (Poland), Prague (Czech Republic), Budapest (Hungary). The current analyses are based on interviews and field research within the Eurofound-financed research project CLIP done in 2008 in those cities in cooperation with local scientific experts, representatives of the ethnic communities and officials of respective Municipalities. It explores which historically and legally established groups are taken in consideration by creating intergroup policy, if the newly arrived immigrants are seen too the target groups for such strategies/policies. And finally, it investigates what types of actors are involved in creating this process and if impulses for actions are coming from a top-down or bottom-up perspective. The main aim of this article is the comparative analysis of 4 cities from CEE countries in order to indicate the similarities and differences in the understanding of intergroup relations in the early stage of development of policy in this field.
Keywords: 330; CEE countries; intergroup policies; local policy-making; migration; Internationale Migration; Interkulturelle Beziehungen; Migrationspolitik; Kommunalpolitik; Estland; Polen; Tschechien; Ungarn